An Assessment of Unused and Regular Use Medicines in Rural Households - Chadalavada, Vineela; Kumar, Lingamguntla Chelmi; Reddy, Edururi Navya Sri; Varma, Mandhapati Vaikunta (Journal of Pharmacy Practice and Community Medicine)
Objectives: Medicines play a crucial role in today's modern lifestyle. It is a known fact that it would be difficult to find a house without medicines. The World health organisation reports that 50% of medicines fall under irrational drug use by humans and majority fail to consume them entirely and correctly. This condition may result in large amounts of leftover medication waste in the households which may be reused or misused, which tends to be dangerous. Our study objective is to find out the proportion of regular and unused medicines present in the households of a rural village in Andhra Pradesh State. Methods: It is a cross-sectional household survey done among 320 households in a rural area of Andhra Pradesh. Data was collected in pre-designed data collection form and analyzed using SPSS software version 16. Results: Among the surveyed households, 252 (78.7%) have unused medication that and a mean of 6.3(±1.5) drug products was found per family. The diseases commonly observed are, Diabetes 114(13.9%), gastrointestinal diseases 112(13.6%), respiratory diseases 104(12.68%) and hypertension 66(8%). The stored drugs found in the households belonged mostly to five categories; Nonsteroidal anti-inflammatory drugs, antibiotics, proton pump inhibitors, antacids and antipyretics. Conclusion: The present study revealed that a significant proportion of rural households had stored unused medicines at home for reusing among family and friends and about none of them had safe storage; hence, is susceptible to various health hazards and accidental poisoning.
Keywords: Household survey; Unused drugs; Irrational drug use; Left over medicines; Reuse of medicines; Unsafe drug use.